2001
DOI: 10.1539/joh.43.271
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lead Exposure in Printing Houses on Immune and Neurobehavioral Functions of Women

Abstract: Effects of Lead Exposure in Printing Houses on Immune and Neurobehavioral Functions of Women: Niu Qiao, et al. Department of Occupational Health, Shanxi Medical University, China—The object of this study was the effect of lead (Pb) exposure on immune and neurobehavioral parameters of 16 women with a mean age of 34 yr who worked for an average of 12 yr in three printing houses in Taiyuan (Shanxi Province, China). The women were not occupationally exposed to toxic agents other than Pb. Mean air Pb in the printin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Alterations in the immune response that can be easily studied in humans are limited and are primarily reflective of changes in circulating leukocyte profiles and Ig concentrations. Some studies of lead-exposed workers have reported lead-associated differences in serum Ig concentrations, percentages of CD4 + T H cells, increased circulating B-lymphocytes, decreased NK cells, and impaired lymphoblastogenesis (Ewers et al 1982;Horiguchi et al 1992;Fischbein et al 1993;Queiroz et al 1993;Undeger et al 1996;Pinkerton et al 1998;Basaran and Undege 2000;El-Safty and Metwally 1995;Kuo et al 2001;Qiao et al 2001;Ayatollahi 2002;Mishra et al 2003Mishra et al , 2006Heo et al 2004;Valentino et al 2007;Mishra et al 2010;Garcia-Leston et al 2011). In contrast, other human investigations at similar BLLs demonstrated opposite or no effects on the same characteristics (Horiguchi et al 1992;Queiroz et al 1994;Pinkerton et al 1998;Heo et al 2004;Mishra et al 2006;Freije and Dairi 2009).…”
Section: Other Studies Consideredmentioning
confidence: 99%
See 3 more Smart Citations
“…Alterations in the immune response that can be easily studied in humans are limited and are primarily reflective of changes in circulating leukocyte profiles and Ig concentrations. Some studies of lead-exposed workers have reported lead-associated differences in serum Ig concentrations, percentages of CD4 + T H cells, increased circulating B-lymphocytes, decreased NK cells, and impaired lymphoblastogenesis (Ewers et al 1982;Horiguchi et al 1992;Fischbein et al 1993;Queiroz et al 1993;Undeger et al 1996;Pinkerton et al 1998;Basaran and Undege 2000;El-Safty and Metwally 1995;Kuo et al 2001;Qiao et al 2001;Ayatollahi 2002;Mishra et al 2003Mishra et al , 2006Heo et al 2004;Valentino et al 2007;Mishra et al 2010;Garcia-Leston et al 2011). In contrast, other human investigations at similar BLLs demonstrated opposite or no effects on the same characteristics (Horiguchi et al 1992;Queiroz et al 1994;Pinkerton et al 1998;Heo et al 2004;Mishra et al 2006;Freije and Dairi 2009).…”
Section: Other Studies Consideredmentioning
confidence: 99%
“…Although studies of the effects of lead exposure on children are plentiful, few have examined effects on the adult immune system, and their results have often been contradictory. There are, however, compelling indications from epidemiologic and worker studies that lead can induce immune alterations in exposed humans (Fischbein et al 1993;Undeger et al 1996;Kuo et al 2001;Qiao et al 2001;Mishra et al 2003;Mishra 2009;Garcia-Leston et al 2011), particularly changes in B lymphocytes; in the nature, extent, and spectrum of circulating antibodies; and in T-lymphocyte profiles. The exact mechanisms whereby lead interacts with the immune system remains unclear.…”
Section: Lamadrid-figureoa Et Al 2007mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, peripheral B lymphocytes were shown decreased in Pb exposed workers (7). Qiao et al (8) reported a reduction of blood NK CD 16+-CD56+ lymphocytes in women chronically Pb-exposed in printing houses. It was suggested that this reduction may depend either on a direct effect of Pb exposure on the immune system or on an effect mediated by the neuroendocrine system.…”
mentioning
confidence: 99%